2003
DOI: 10.1002/cncr.11835
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in protection against adenocarcinoma of the cervix resulting from participation in cervical screening

Abstract: This article presents a fleet‐wide model for energy planning that can be used to determine the optimal structure necessary to meet a given CO2 reduction target while maintaining or enhancing power to the grid. The model incorporates power generation as well as CO2 emissions from a fleet of generating stations (hydroelectric, fossil fuel, nuclear, and wind). The model is formulated as a mixed integer program and is used to optimize an existing fleet as well as recommend new additional generating stations, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…This was attributed to the change in the sampling device used; the endocervical brush was introduced to replace the spatula that focused only on the sampling of squamous cells. In a study of the screening history and risk of AC, it was concluded that AC incidence should begin to decline in the current decade among screened women (Mitchell et al, 2003). Our study included data from 1989 to 2003, the second study to incorporate years after 2000 (Howlett et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the change in the sampling device used; the endocervical brush was introduced to replace the spatula that focused only on the sampling of squamous cells. In a study of the screening history and risk of AC, it was concluded that AC incidence should begin to decline in the current decade among screened women (Mitchell et al, 2003). Our study included data from 1989 to 2003, the second study to incorporate years after 2000 (Howlett et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of Victorian Cervical Cytology Registry data published in 2003, found that the Pap smear did confer significant protection against being diagnosed with invasive adenocarcinoma. 16 The role of HPV It has been established that HPV is a necessary cause of cervical cancer. 17 The International Agency for Research on Cancer has identified HPV type 16 (HPV-16), HPV-18, HPV-31, HPV-33, HPV-35, HPV-39, HPV-45, HPV-51, HPV-52, HPV-56, HPV-58, HPV-59 and HPV-66 as oncogenic types for the cervix.…”
Section: Histological Typementioning
confidence: 99%
“…Whereas effective cytologic screening has led to declines in cervical squamous cell carcinoma incidence and mortality rates among targeted age groups over the same time period, the intervention has been considered less effective at reducing the incidence of cervical adenocarcinoma (64). Some authors have, however, suggested that screening may have been responsible in some reductions in adenocarcinoma during the 1990s (15,29). Mitchell et al (29) observed decreases among Australian women who had a pap smear with endocervical material within 1 year, or with an increasing number of pap smears with an endocervical component.…”
Section: Is the Increasing Risk In Recent Successive Generationsmentioning
confidence: 99%
“…Some authors have, however, suggested that screening may have been responsible in some reductions in adenocarcinoma during the 1990s (15,29). Mitchell et al (29) observed decreases among Australian women who had a pap smear with endocervical material within 1 year, or with an increasing number of pap smears with an endocervical component. One explanation for an increasing ability to detect endocervical lesions in cervical screening involves the improved diagnostic yield via use of the extended tip spatula or the Cervex (endocervical) brush, or a combination of both (65), as well as an understanding and recognition of adenocarcinoma in situ (30).…”
Section: Is the Increasing Risk In Recent Successive Generationsmentioning
confidence: 99%